Interfaith dialogue: moving forward; setting premises and paradigms - Kamaruzaman, Kamar Oniah (Vista Publications, 2001)
Interfaith dialogue is necessary today. Obstacles to dialogue. Formulating Premises for Dialogue - interfaith dialogue, interfaith cooperation. Paradigms of Dialogue - ethics and etiquettes of dialogue.